The Savvy Survey #12: Telephone Surveys - Glenn D. Israel; Jessica L. Gouldthorpe (EDIS, 2014)
This publication provides a brief overview of how to develop and conduct a telephone survey to collect data. It assumed that a list of phone numbers, such as program registration lists, is available for conducting program evaluations or assessing needs. When volunteers or staff assist with the survey by interviewing respondents, this data collection method can be economical and effective. Careful attention is needed when developing the questionnaire and supporting materials and when orienting interviewers in order to obtain credible survey data. In the right situation, telephone surveys can be a valuable tool for Extension agents and specialists. This 7-page fact sheet was written by Glenn D. Israel and Jessica L. Gouldthorpe, and published by the UF Department of Agricultural Education and Communication, October 2014.